Deteksi Microaneurysms Pada Citra Retina Mata Menggunakan Matched Filter - Muhammad Santoso; Tutuk Indriyani; Ricky Eka Putra (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2017)
Diabetic retinopathy is one of diabetes mellitus on eyes which causes permanent blindness. Microaneurysm becomes its sympthom which is signed by a spot with dark red in circle shape. A detection system on microaneurysms is designed to help medical experts. This research employed matched filter method to detect microaneurysms. Matched filter refers to one of matching template techniques. Microaneurysms have intencity profile in Gaussian, therefore a Gaussian matched filter can be used for detecting them. The searching on the sensitivity, specificity, and accuracy was calculated by ROC (Receiver Operating Characteristics). The research results obtained from 30 retina images of DIAETDB1 showed the average levels of sensitivity 64.53%, specificity 99.94%, and accuracy 99.90%.Keywords: Diabetic Retinopathy, Microaneurysm, Matched Filter, Gaussian Matched Filter, ROC, DIARETDB1.